An Examination of the Impact of Relative Age Effects and Academic Timing on Intercollegiate Athletics Participation in Women's Softball - Jess C. Dixon; Vincenzo Liburdi; Sean Horton; Patricia L. Weir (University of Kansas Libraries, 2013)
This investigation makes three noteworthy contributions to literature on the Relative Age Effect (RAE); 1) it adds to the small number of studies in women's sports, 2) it is one of very few papers to examine the RAE in intercollegiate athletics, and 3) it (re-)introduces "academic timing" to the discussion of RAEs in this context. The 50 top-ranked NCAA Division I women's softball teams at the conclusion of the 2011 season served as the focus for this investigation. Student-athletes were grouped into quartiles according to their birth date and identified as "on-time" or "academically delayed" based on their birth year and eligibility status. On-time student-athletes were over four times more likely to be born in quartile one than in quartile four, demonstrating a traditional RAE. This pattern was reversed for those who were academically delayed, with quartile four birth dates constituting more than half of the entire sample.